2003
DOI: 10.1002/etc.5620220623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the androgenic growth promoter 17‐β‐trenbolone on fecundity and reproductive endocrinology of the fathead minnow

Abstract: Trenbolone acetate is a synthetic steroid that is extensively used in the United States as a growth promoter in beef cattle. The acetate is administered to livestock via slow-release implants; some is converted by the animal to 17-beta-trenbolone, a relatively potent androgen receptor agonist in mammalian systems. Recent studies indicate that excreted 17-beta-trenbolone is comparatively stable in animal waste, suggesting the potential for exposure to aquatic animals via direct discharge, runoff, or both. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
331
5
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 349 publications
(367 citation statements)
references
References 43 publications
25
331
5
6
Order By: Relevance
“…17b-trenbolone is a strong androgen receptor agonist that depresses VTG production. Exposure to 17b-trenbolone at concentrations similar to those found in the environment decreases egg production in female FHMs and produces changes in plasma concentrations of 17b-estradiol, testosterone, and VTG (Ankley et al 2003). Increasing 17b-trenbolone exposure concentrations results in "U-shaped" responses for plasma 17b-estradiol, testosterone, and VTG concentrations (Ankley et al 2003).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…17b-trenbolone is a strong androgen receptor agonist that depresses VTG production. Exposure to 17b-trenbolone at concentrations similar to those found in the environment decreases egg production in female FHMs and produces changes in plasma concentrations of 17b-estradiol, testosterone, and VTG (Ankley et al 2003). Increasing 17b-trenbolone exposure concentrations results in "U-shaped" responses for plasma 17b-estradiol, testosterone, and VTG concentrations (Ankley et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…The experimental designs and corresponding data summaries were described by Watanabe et al (2007). Among the 13 studies, one was a baseline reproduction study in unexposed (baseline) FHMs , and the rest were reproduction studies in which FHMs were exposed to 12 EDCs, including methoxychlor and methyltestosterone , fadrozole (Ankley et al 2002), 17b-trenbolone (Ankley et al 2003), flutamide (Jensen et al 2004), prochloraz and fenarimol (Ankley et al 2005a), perfluorooctane sulfonate (Ankley et al 2005b), 17a-trenbolone , prometon , ketoconazole , and haloperidol (Villeneuve et al 2010). For modeling purposes, we used fecundity data from the baseline reproduction study (data I), the control FHMs from the 12 EDC exposure experiments (data II), and FHMs exposed to 17b-trenbolone (data III) (Ankley et al 2003).…”
Section: Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…R. Soc. B 369: 20140022 [24,27,30,31] anti-androgens androgen receptor antagonism -impaired ovulation and spawning -impaired sexual differentiation -decreased nest defence -reproductive impairment -reduced probability of young of year survival** [32 -37] hormonal contraceptive oestrogen receptor activation -impaired ovulation and spawning -impaired sexual development -reproductive impairment [27] hormonal contraceptive oestrogen receptor antagonism* -impaired vitellogenesis, ovulation and spawning -impaired sexual differentiation -reproductive impairment** [38 -42] hormonal contraceptive progesterone receptor activation -reduced fecundity -reduced sperm motility -reproductive impairment [43 -46] anti-inflammatory glucocorticoid receptor activation -reduced oestradiol synthesis and fecundity -morphological abnormalities -decreased immune response -reproductive impairment -reduced probability of young of year survival** [47 -49] anti-depressants serotonin reuptake inhibition -morphological abnormalities -reduced fecundity -decreased food intake -impaired predator avoidance -reproductive impairment -reduced probability of young of year survival** [50 -55] anti-convulsant gamma-aminobutyric-acid receptor opening** sodium-channel inhibition -impaired predator avoidance -reduced probability of young of year survival** [56,57] non-steroidal anti-inflammatory drugs cyclooxygenase inhibition -impaired growth -impaired hatching -decreased spawning behaviour a -reduced fecundity a -increased probability of mortality** -reduced probability of young of year survival** -impaired reproduction a [58 -60] fibrates peroxisome proliferator-activated receptor activation -reduced fecundity -impaired reproduction [61] beta-blockers beta-adrenergic receptor antagonist -reduced growth -reduced probability of young of year survival** -increased probability of mortality** [62 -64] Aromatase inhibition is an established molecular initiating event for propiconazole, however other conazoles have been shown to inhibit other cytochrome P450 enzymes [76].…”
Section: (B) Conservation Of Molecular Target For Cross-species Extramentioning
confidence: 99%
“…More recently, studies have also reported traces of natural estrogens and androgenic steroid hormones at concentrations of a few nanograms per liter (ng/L) in river water and estuaries downstream from wastewater treatment facilities (Snow et al 2013). Mounting evidence indicates that steroid hormones can affect wildlife by causing non-lethal but adverse ecological health effects even though at low levels in the environment (Ankley et al 2003;Jensen et al 2006;Jobling et al 1998;Kidd et al 2007). Therefore, it is critical to analyze the occurrence and to study the fate and transport of these steroid hormones in environment.…”
Section: Introductionmentioning
confidence: 97%